Phenology, Seed Germination, and Genetics Explains the Reproductive Strategies of Diospyros lasiocalyx (Mart.) B. Wall - Aguiar, Bruna Ibanes; Sebbenn, Alexandre Magno; Tarazi, Roberto; Vogado, Nara Oliveira [UNESP]; Morellato, Leonor Patrícia Cerdeira [UNESP]; Tambarussi, Evandro Vagner; Moreno, Maria Andréia; Pereira, Lya C. S. M.; Montibeller, Cinthia; Ferraz, Elza Martins; Gandara, Flávio Bertin; Kageyama, Paulo Yoshio (Springer Nature, 2020)
Diospyros lasiocalyx (Mart.) B. Wall. is a dioecious tree species found in the threatened and fragmented Brazilian Cerrado. Its fleshy fruits, which are consumed extensively by wildlife, make the species ideal for use in restoration. This study includes a ten-year phenological observation, germination tests, and analysis of molecular markers to understand the reproductive strategy of D. lasiocalyx based on samples from three populations in two Cerrado ecosystems in São Paulo State, Brazil. The within population reproductive phenological pattern presented low synchrony, indicating a lack of sexual reproduction. The vegetative phenological pattern was well pronounced, with the peak of senescence occurring at the end of the dry season, just before leaf flushing. A small number of unique genets were found, indicating asexual reproduction and low genotypic diversity in the studied populations. The absence of inbreeding and the presence of ramets (stems) suggest that reproduction mainly occurs by apomixis and vegetative propagation, with some mating among unrelated stems and a low germination rate. Our study indicates that D. lasiocalyx can colonize harsh environments such as the Cerrado using alternative asexual reproductive strategies, while simultaneously attracting many seed dispersers.
Keywords: Genotypic diversity; Microsatellite markers; Population genetics; Tropical tree species; Vegetative and reproductive phenology